An equality perspective on residential child care - Niall Hanlon (Scottish Journal of Residential Child Care, 2007)
An equality perspective on residential child care is one which places the issues of power and oppression as central concerns of practice. This requires more than an understanding and appreciation of the nature of the inequalities that children in care experience. The residential practitioner must appreciate egalitarian values and develop the skills, competences and knowledge base to evolve programmes and strategies that promote equality. Fundamentally, equality practices require significant changes in relationships of power. This paper will outline a means of conceptualising inequalities by discussing the way that they often have an impact on children and young people in residential care.